Collected Works of Paul Valery. - Valéry, Paul (Princeton legacy library., 2017)
This is an informal collection of essays and speeches on the writers who in one way or another counted for Valéry in the shaping of his mind or in his affections and interests: Descartes, Voltaire, Stendhal, Goethe, Villon, Nietzsche, Pascal, Proust, Huysmans, Pierre Louÿs, Nerval, Rilke, Bergson, and others. The volume presents, in an appendix, the first publication in English of any extensive selection from Valéry's personal notebooks--the Cahiers. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.